Marketing redefined: A qualitative and integrative literature review charting the evolution of marketing definitions - Norman Mafuratidze; Professor Marius Wait; Professor Ilse Struweg (The Retail and Marketing Review)
Purpose: This study uses the integrative literature review (ILR) methodology to examine the evolution of marketing definitions through technological transformation, demonstrating ILR's unique capacity to synthesise diverse sources and reveal thematic developments in marketing's progression.